Evolutionary anatomy of the primate cerebral cortex - Falk, Dean; Gibson, Kathleen R (Cambridge University Press, 2001)
Studies of brain evolution have moved rapidly in recent years, building on the pioneering research of Harry J. Jerison. This book provides state-of-the-art reviews of primate (including human) brain evolution. The volume is divided into two sections, the first offers new perspectives on the developmental, physiological, dietary, and behavioral correlates of brain enlargement. However, it has long been recognized that brains do not merely enlarge globally as they evolve, but that their cortical and internal organization also changes in a process known as reorganization. Species-specific adaptations therefore have neurological substrates that depend on more than just overall brain size. The second section explores these neurological underpinnings for the senses, adaptations, and cognitive abilities that are important for primates. With a prologue by Stephen J. Gould and an epilogue by Harry J. Jerison, this is an important new reference work for all those working on primate brain evolution.
Keywords: Cerebral Cortex; neurologie; mozková kůra